Theory of networks and processes: A first foundation of process networks - Heinrich Seidlmeier (Technische Hochschule Rosenheim, 2023)
The impulse to think about process-induced social networks (in short: process networks) comes from the discipline of "Process Mining" (e.g. van der Aalst et al. 2005). The relevant literature refers to an "organizational view" or "organizational mining" in process mining. In essence, process mining is about creating a time-logical chain of related tasks from automatically logged user activities on a computer. In this way, real processes can be mapped and analyzed as models. As a "by-product", task-related social networks are created between the process participants through the predecessor/successor relationships in the workflow. However, it should be noted and criticized that process mining research neglects the potential of social network analysis. The extensive findings of classical network research are not taken up further. An organizational and social scientific deepening of the data-driven preliminary work is missing in this discipline. Process mining, which tends to be mathematical and technical, has not yet developed the ambition to ally itself with empirical organizational and social research. This working paper tries to counteract this. It presents a first, social science-based approach to theoretically grounding process networks.
urn:nbn:de:bvb:861-opus4-22127
Keywords: 650; Business Process; Process Management; Social Network; Process Theory